2013
DOI: 10.4172/2161-0932.1000186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porcine Placental Extract on Collagen Production in Human Skin Fibroblasts In Vitro

Abstract: Placental Extract (PE) has been used as a folk remedy in Asian countries. Human PE is clinically used for the treatment of skin wrinkles because it promotes skin regeneration. In this study, we found that Porcine PE (PPE) promoted collagen production in Normal Human Dermal Fibroblasts (NHDFs). Treatment of NHDFs with PPE at concentrations of 12.5-100 μg/mL enhanced their proliferation and secretion of procollagen C peptide. We also found that expression of intracellular Matrix Metalloproteinase-9 (MMP-9) in PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…We previously reported that HGFs shows a similar cell proliferation tendency under the same P-placenta concentration 8) . Yoshikawa et al reported that 0-100 g/ml Pplacenta elevated the proliferation of human skin fibroblasts 18) .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that HGFs shows a similar cell proliferation tendency under the same P-placenta concentration 8) . Yoshikawa et al reported that 0-100 g/ml Pplacenta elevated the proliferation of human skin fibroblasts 18) .…”
Section: Discussionmentioning
confidence: 99%
“…The placenta extract is scientifically proven skin-whitening effect [7] [11] [13] and reduces oxidative stress. It also induces fibroblast proliferation and collagen synthesis [10]. It could inhibit melanin synthesis and also regulate antioxidant genes and might protect the skin against oxidative stress [14] [15] [16].…”
Section: Discussionmentioning
confidence: 99%
“…Yoshikawa et al . ( Yoshikawa et al ., 2013 ) demonstrated that oral PPE treatment may be used to improve skin wrinkles. Oral PPE treatment in postmenopausal women leads to a decrease in the width of wrinkles.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that PPE drives skin fibroblasts into the S phase and increases the basic fibroblast growth factor level ( Pal et al ., 2002 ). It significantly increases collagen production in dermal fibroblasts, suggesting that it has a stimulatory effect on collagen production ( Yoshikawa et al ., 2013 ). Skin collagen has a central role in the mechanical strength of skin, as a component of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%